INTERRELATIONS BETWEEN HUMAN RIGHTS AND INTERNATIONAL HUMANITARIAN LAW ACCORDING TO SEPARATION WALL CASE - Kristianti, Wulan (Indonesian Journal of International Law, 2021)
According to the ICJ, Israel has violated International Human Rights Law (IHRL) namely the right to liberty of movement under the 1966 International Covenant on Civil and Political Rights (ICCPR), the right to work, the right to health, the right to education, and to an adequate standard of living under the 1966 International Covenant on Economic, Social and Cultural Rights (ICESCR) and the 1989 Convention on the Rights of the Child (CRC). This paper will discuss whether those norms are also covered under International Humanitarian Law (IHL) applicable in the occupied territory. It is without doubt that Geneva Convention IV in the occupied territory applies since the military occupation occurred and the victims who are the Palestinian inhabitants are regarded as protected persons. Israel has not become a party to the 1977 Additional Protocol I, consequently, those provisions do not apply unless those provisions are considered customary law.